Public entrepreneurship and sub-clinical psychopaths: a conceptual frame and implications. Issue 6 (8th August 2016) - Fennimore, Anne; Sementelli, Arthur
Abstract : Purpose: The purpose of this paper is to adapt the research conducted on subclinical psychopaths in the private sector and applies it to the public sector to build a conceptual frame for further research on subclinical psychopaths in public organisations. General characteristics of entrepreneurs often run counter to democratic values, and are more often aligned with private sector values. Public managers who display one of the dark-triad personalities, i.e., psychopathy, can pose a greater threat to democratic values and the state. Design/methodology/approach: The approach of this paper is theoretical with the aim of proposing a conceptual framework that utilises Downs' five types of officials governing bureaucracies, to illustrate a relationship between public entrepreneurs and subclinical psychopaths. Findings: The conceptual framework presented in this paper suggests that psychopathic entrepreneurs can be identified within Downs' bureaucratic framework specifically as climbers (due to inherent personality traits) and as zealots (heroic and altruistic behaviour for organisational causes, yet motivated by power, domination, and self-interest). The implications of psychopathic public managers who engage in entrepreneurial activities may be escalating public distrust, hostility, and dissatisfaction in government. Originality/value: This theoretical paper adds to the growing body of criticism for public entrepreneurship by conceptualising how psychopaths, as climbers and zealots, affect public trust in terms of accountability and democratic values.